FRI0457 LONG-TERM OUTCOMES AND TREATMENT EFFICACY IN PATIENTS WITH TNF RECEPTOR-ASSOCIATED AUTOINFLAMMATORY SYNDROME (TRAPS) FROM THE EUROFEVER INTERNATIONAL REGISTRY. (2nd June 2020) - Papa, R.; Lane, T.; Bovis, F.; Minden, K.; Touitou, I.; Cantarini, L.; Cattalini, M.; Obici, L.; Jansson, A.; Belot, A.; Woska-Kuśnierz, B.; Berendes, R.; et al.
Abstract : Background: Tumour necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) is one of the best-known monogenic auto-inflammatory disorders resulting from an autosomal dominant variation in the TNF super family receptor 1A ( TNFRSF1A ) gene (1). Objectives: To define best treatment approach in patients with TRAPS and effect on long-term outcomes. Methods: We reviewed all data on patients with TRAPS enrolled in the Eurofever international registry according the INSAID gene variant classification and the new Eurofever/PRINTO classification criteria (EPCC). Results: Data on 226 patients were available. Patients not fulfilling the EPCC carrying likely benign/benign variants (21 patients, 9%) or VOUS/not classified variants (40 patients, 18%) displayed a milder disease than the patients fulfilling the EPCC with VOUS/not classified variants (38 patients, 17%) or pathogenic/likely pathogenic variants (127 patients, 56%). In particular, in patients not fulfilling the EPCC, less frequent abdominal pain and skin rashes, higher efficacy rate of colchicine and no development of AA amyloidosis have been reported. Almost 90% of patients fulfilling the EPCC required maintenance therapy and anti-interleukin (IL)-1 drugs were the most frequently used, with the highest efficacy rate (>85% complete response), while Etanercept was less effectively used and discontinued in 65% of patients. Conclusion: Anti-IL-1 drugs are the best maintenance treatment in TRAPS with potential to reverse the most serious disease complications of AA amyloidosis and infertility. The diagnosis of TRAPS should be considered very carefully in patients carrying VOUS/not classified variants not fulfilling the EPCC. References: [1]Lachmann HJ, Papa R, Gerhold K, Obici L, Touitou I, Cantarini L, et al. The phenotype of TNF receptor-associated autoinflammatory syndrome (TRAPS) at presentation: a series of 158 cases from the Eurofever/EUROTRAPS international registry. Annals of the rheumatic diseases 2014;73:2160-7. Acknowledgments: RP would like to thank the European Federation of Immunology (EFIS) for the short-term bursary and HL for her continuous support and guidance during the fellowship at the National Amyloidosis Centre in London. Disclosure of Interests: Riccardo Papa: None declared, Thirusha Lane: None declared, Francesca Bovis: None declared, Kirsten Minden Consultant of: GlaxoSmithKline, Sanofi, Speakers bureau: Roche, Isabelle Touitou: None declared, Luca Cantarini: None declared, Marco Cattalini: None declared, Laura Obici: None declared, Annette Jansson: None declared, Alexander Belot: None declared, Beata Woska-Kuśnierz: None declared, Rainer Berendes: None declared, Agustin Remesal: None declared, Marija Jelusic: None declared, Graciela Espada: None declared, Irina Nikishina: None declared, Esther Hoppenreijs: None declared, Maria Cristina Maggio: None declared, Taryn Youngstein: None declared, Tamer Rezk: None declared, Charalampia Papadopoulou: None declared, Paul Brogan Grant/research support from: Roche, Novartis, SOBI, Chemocentryx, Novimmune, Consultant of: Roche, SOBI, UCB, Novartis, Speakers bureau: Roche, SOBI, UCB, Novartis, Philip N Hawkins: None declared, Patricia Woo: None declared, Nicolino Ruperto Grant/research support from: Bristol-Myers Squibb, Eli Lily, F Hoffmann-La Roche, GlaxoSmithKline, Janssen, Novartis, Pfizer, Sobi (paid to institution), Consultant of: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda, Speakers bureau: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda, Marco Gattorno Consultant of: Sobi, Novartis, Speakers bureau: Sobi, Novartis, Helen J. Lachmann: None declared